Method for preparing sodium vanadium fluorophosphate / carbon composite positive electrode material by one-pot method and application of sodium vanadium fluorophosphate / carbon composite positive electrode material

Synthesizing sodium vanadium fluorine phosphate/carbon composite positive electrode material by one-pot microwave hydrothermal method, solving the problems of low structural stability and rate performance of sodium ion battery materials, and achieving efficient and uniform sodium vanadium fluorine phosphate/carbon composite material Prepared, suitable for sodium ion batteries, reducing energy consumption and cost.

CN119284877APending Publication Date: 2025-01-10QINGDAO SAILIDA ENERGY STORAGE IND TECHNOLOGY RESEARCH INSTITUTE CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411414948.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing sodium ion battery cathode materials face many challenges in their practical application due to poor structural stability, slow ion diffusion kinetics, low working voltage and low energy density. In particular, the complication of sodium vanadium fluorine phosphate and the high temperature calcination leads to fluorine loss. The uneven coating of carbon and carbon affects the rate performance.

Method used

A one-pot microwave hydrothermal method is used to synthesize sodium vanadium phosphate/carbon composite cathode material. The vanadium source, reducing agent, carbon source, phosphorus source, sodium source and fluorine source are chemically employed under microwave conditions of 160℃ to 220℃. Metered mixing to form a transparent solution and reacted in a microwave hydrothermal parallel synthesizer followed by natural cooling and vacuum drying, simplifying the synthesis steps and improving the uniformity and purity of the material.

Benefits of technology

The reaction time is shortened, the purity and crystallinity of sodium vanadium fluorophosphate is improved, the carbon coating is more uniform, the rate performance of the material is significantly improved, and energy consumption and cost are reduced. It is suitable for sodium ion battery positive electrode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119284877A_ABST
    Figure CN119284877A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sodium ion battery positive electrode materials, in particular to a synthesis method and application of a sodium vanadium fluorophosphate / carbon composite positive electrode material prepared by a one-pot method. The preparation method specifically comprises the following steps: mixing and dissolving raw materials for synthesizing sodium vanadium fluorophosphate, a reducing agent and a carbon source to form a transparent solution, and reacting the solution under a microwave condition of 160-220 DEG C to obtain the sodium vanadium fluorophosphate / carbon composite positive electrode material. According to the method, the sodium vanadium fluorophosphate / carbon composite positive electrode material is synthesized by adopting a'one-pot method 'microwave hydrothermal assistance, the carbon-coated sodium vanadium fluorophosphate positive electrode material which is extremely high in purity and high in yield can be obtained, the synthesis steps and the reaction time are greatly reduced, and the positive electrode material has excellent rate capability when being applied to the sodium-ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sodium ion battery positive electrode materials, and in particular to a method for preparing sodium vanadium fluorophosphate / carbon composite positive electrode material by a one-pot process and application thereof. Background Art

[0002] At present, renewable energy (such as solar energy, wind energy, tidal energy, etc.) is completely dependent on the environment, and environmental resources are uncertain and unstable. Therefore, the development of safe and efficient energy storage technology is conducive to the development of renewable energy. Lithium-ion batteries are widely used in power batteries and energy storage due to their high energy density, but the limited and uneven distribution of lithium resources has caused the continuous fluctuation of lithium carbonate prices, and the cost issue has brought great challenges to the energy storage field. Sodium-ion batteries, thanks to their abundant resources and low cost advantages, are expected to solve the problems of lithium resource scarcity and price fluctuations.

[0003] At present, the cathode materials of sodium-ion batteries pose great challenges to the practical application of sodium-ion batteries due to their poor structural stability, slow ion diffusion kinetics, low operating voltage and low energy density. Common cathode materials for sodium-ion batteries mainly include layered transition metal oxides, Prussian blue analogs and polyanion compounds. Layered transition metal oxides have improved reversibility through element doping, substitution, interface modification and other means, but they still have problems such as poor lattice stability and low average operating voltage; Prussian blue materials have many structural defects and high lattice water content, which will have various adverse effects on the performance of sodium-ion batteries; polyanion compounds have better cycle stability and are more widely used in sodium-ion battery cathode materials.

[0004] Among polyanionic compounds, sodium vanadium phosphate (Na3V2(PO4)3) is widely used as a cathode material for sodium ion batteries. Its lattice allows ultrafast and stable sodium insertion and extraction. However, the operating voltage platform of sodium vanadium phosphate cathode is only 3.3-3.4V, and the theoretical energy density is only about 394Wh kg -1 This value is much lower than that of the commercially representative lithium-ion battery cathode material (LiFePO4 cathode is about 500-530Wh kg -1 ), so improving the working voltage and energy density is the key issue facing the positive electrode materials of sodium ion batteries. An effective strategy to solve this problem is to introduce highly electronegative anions fluoride ions, replace the VO bond with a VF bond, and become sodium vanadium fluorophosphate (Na3V2(PO4)2F3), which causes Na to produce a higher redox potential during the insertion and extraction process as the V valence changes. Uniform carbon coating can further improve the conductivity of sodium vanadium fluorophosphate, increase the electron transfer rate, and give it better rate performance.

[0005] At present, the synthesis of sodium vanadium fluorophosphate usually uses solid phase method, sol-gel method, solvothermal method, etc. Although the solid phase method is simple to operate and easy to industrialize, it has the disadvantages of long calcination time, slightly poor sample uniformity and performance, and high temperature calcination may cause fluorine loss; the sol-gel method can reduce the calcination temperature and time by mixing the precursors evenly, but it is easy to leave in-situ carbon under inert gas; the solvothermal method has a low synthesis temperature and low energy consumption, but the reaction conditions are not easy to control and the yield is low. The patent document with application number CN 201711090279.7 discloses a method of obtaining sodium vanadium fluorophosphate / carbon composite positive electrode material by solvothermal-ball milling method. The application first synthesizes sodium vanadium fluorophosphate by solvothermal method, and then uses ball milling to achieve carbon coating. There are problems such as complicated steps, long time consumption, and uneven physical carbon coating, which increases energy consumption and affects the improvement of rate performance. Summary of the invention

[0006] In order to solve the problems of the prior art, the present invention aims to provide a method and application of preparing sodium vanadium fluorophosphate / carbon composite positive electrode material by a one-pot process.

[0007] To achieve the above purpose, the present invention adopts the following technical solution:

[0008] A one-pot method for preparing sodium vanadium fluorophosphate / carbon composite positive electrode material comprises mixing raw materials for synthesizing sodium vanadium fluorophosphate according to stoichiometric amounts, adding a reducing agent and a carbon source, mixing and dissolving to form a transparent solution, and then reacting the solution under microwave conditions at 160° C. to 220° C. to obtain the sodium vanadium fluorophosphate / carbon composite positive electrode material.

[0009] Furthermore, the vanadium source and the reducing agent in the synthetic sodium vanadium fluorophosphate are mixed and dissolved with deionized water, and a carbon source is added during the dissolution until a homogeneous solution is formed, and then a phosphorus source, a sodium source and a fluorine source are added in sequence according to the stoichiometric amount and stirred to form a transparent solution, and the solution is reacted at 160° C. to 220° C. under microwave conditions, and after the reaction is completed, it is naturally cooled to room temperature, centrifuged multiple times with deionized water and ethanol, and then vacuum dried to obtain the final product.

[0010] Going further,

[0011] (1) preparing a precursor reaction solution: mixing a vanadium source and a reducing agent with deionized water, heating and stirring until completely dissolved, adding a carbon source during the complete dissolution process, and continuing to stir until a homogeneous solution is formed, and then adding a phosphorus source, a sodium source, and a fluorine source to the homogeneous solution, and continuing to stir under the above heating conditions until completely dissolved into a transparent solution, and adjusting the system to a weak acid after a transparent solution is formed;

[0012] (2) Microwave hydrothermal synthesis of precursor products: The transparent solution obtained in step (1) is placed in a microwave hydrothermal parallel synthesizer, heated to 160°C to 220°C, reacted under microwave conditions, cooled to room temperature after the reaction, centrifuged multiple times with deionized water and ethanol, and the precipitate after centrifugation is vacuum dried to obtain a sodium vanadium fluorophosphate / carbon composite positive electrode material.

[0013] In the step (1), during the process of forming a transparent solution, the heating temperature and stirring conditions of each dissolution process are the same, the heating temperature is 60-80° C., and the stirring condition is 250-800 rpm.

[0014] The concentration of vanadium in the system in step (1) is controlled at 0.33 to 1.80 mol·L -1 The concentration of the reducing agent is controlled at 0.83~5.76mol·L -1 , carbon source concentration is 0.11~1.60mol·L -1 The concentration of phosphate is 0.17~1.60mol·L -1 The concentration of fluorine source is 0.83~5.76mol·L -1 , the concentration of sodium source is 0.83~5.76mol·L -1 .

[0015] The vanadium source is one or more of vanadium pentoxide, ammonium metavanadate, sodium vanadate and sodium metavanadate; the reducing agent is oxalic acid or citric acid; the carbon source is glucose or sucrose; the phosphorus source is one or more of ammonium dihydrogen phosphate, diammonium hydrogen phosphate and sodium dihydrogen phosphate; the fluorine source is sodium fluoride or ammonium fluoride; the sodium source is one or more of a substance containing sodium in a vanadium source, a phosphorus source or a fluorine source, sodium oxalate, sodium carbonate, sodium bicarbonate. When the sodium source is a substance containing sodium in a vanadium source, a phosphorus source or a fluorine source, and it meets the stoichiometric ratio, there is no need to add a sodium source.

[0016] In step (1), hydrochloric acid, sulfuric acid, nitric acid, acetic acid or lactic acid may be used to adjust the system to a weak acid state, and the pH value may be adjusted to a range between 3.0 and 6.0.

[0017] In the step (2), the volume ratio of the transparent solution to the reactor of the microwave hydrothermal parallel synthesizer is (35-60):100; the microwave frequency is 2450 MHz, the reaction temperature is 160° C.-220° C., and the reaction time is 60 min-120 min.

[0018] The centrifugation times in step (2) are no less than 3 times, and better results can be achieved if the centrifugation times are controlled between 3 and 6 times. The vacuum drying temperature is controlled between 60 and 90°C, and should not be too high.

[0019] A method for preparing the sodium vanadium fluorophosphate / carbon composite positive electrode material is used in sodium ion batteries.

[0020] The battery uses the Na3V2(PO4)2F3 / C composite prepared as above as the positive electrode, metallic sodium as the negative electrode, and glass fiber as the separator, which is suitable for the electrolyte of existing sodium ion batteries. The positive electrode uses aluminum foil as the current collector to assemble into a sodium ion battery.

[0021] Beneficial effects of the present invention:

[0022] The traditional hydrothermal method for synthesizing sodium vanadium fluorophosphate needs to be carried out under high temperature and high pressure, and the reaction time is 20 hours. The subsequent ball milling, high temperature calcination, and carbon coating make the preparation process cumbersome and the high temperature calcination causes the loss of fluorine. At the same time, the physical carbon coating is uneven, which affects the improvement of the rate performance. The "one-pot method" of the present invention combines the synthesis step and the carbon coating step into one to obtain sodium vanadium fluorophosphate / carbon. This method shortens the reaction time to the greatest extent, and due to the unique heating method of the microwave hydrothermal method, the solution itself becomes a heating element, and no heat conduction process is required, which overcomes the disadvantage of uneven heating of the traditional hydrothermal method. At the same time, the method of uniformly penetrating electromagnetic waves inside and outside the present invention to generate heat energy further promotes the growth of crystal nuclei. The synthesized sodium vanadium fluorophosphate has higher purity, better crystallinity, and more uniform carbon coating, which makes the material have better rate performance, while reducing energy consumption and cost, so that the "one-pot method" of the present invention has a good application prospect. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a schematic diagram of the "one-pot" microwave hydrothermal assisted synthesis of sodium vanadium fluorophosphate / carbon positive electrode material provided by an embodiment of the present invention.

[0024] Figure 2 It is the XRD diagram of NVPF / C-190-1 of Example 1 of the present invention and the powder of Comparative Example 2.

[0025] Figure 3 It is a cycle diagram of different rates of batteries composed of the positive electrode synthesized by NVPF / C-190-1 of Example 1 of the present invention and the positive electrode synthesized by Comparative Example 1 and the sodium negative electrode.

[0026] Figure 4 It is a charge and discharge curve diagram of a battery composed of NVPF / C-210-3 and a sodium negative electrode in Example 3 of the present invention.

[0027] Figure 5 It is a cycle diagram of a battery composed of NVPF / C and a sodium negative electrode in comparative example 2 of the present invention at different rates. DETAILED DESCRIPTION

[0028] In order to better illustrate the content of the invention, the following examples further verify the present invention, and the examples are only a part of the present invention and cannot constitute any limitation to the present invention.

[0029] The present invention utilizes a microwave-assisted one-pot method to realize the integration of sodium vanadium fluorophosphate synthesis and carbon coating, and simultaneously controls the reaction conditions and the pH value of the system and adopts a microwave uniform heating method to make the sodium vanadium fluorophosphate / carbon composite positive electrode material higher in purity, and the liquid phase in-situ carbon coating is more uniform, and the sodium vanadium fluorophosphate / carbon composite positive electrode material with excellent rate performance is synthesized while reducing the reaction time and energy consumption.

[0030] Example 1

[0031] The synthesis method of sodium vanadium fluorophosphate / carbon composite positive electrode material in this example is shown in Figure 1 The specific steps include:

[0032] (1) Prepare the precursor reaction solution: Mix 20 mmol V2O5 and 50 mmol H2C2O4 (molar ratio 1:2.5), add deionized water to make the volume 40 mL, control the temperature to 70 °C water bath heating for 10 min, add 1 g C6H 12 O6 (carbon source concentration is 0.11 mol·L -1 ), continue stirring for 10 min until it is completely dissolved, then add 40 mmol NH4H2PO4 and 60 mmol NaF (molar ratio, phosphate: vanadium = 1:1, sodium: vanadium = 3:2, fluorine: vanadium = 3:2) in sequence, continue to heat and stir in a 70°C water bath to obtain a transparent dark blue solution, add water to make the volume to 45 mL, after the temperature drops to room temperature, add 3 times diluted 15% concentrated hydrochloric acid dropwise to the dark blue solution, and adjust the pH to 3.2.

[0033] (2) The solution obtained in step (1) was placed in a reactor of a microwave hydrothermal parallel synthesizer, with the volume ratio of the solution to the container being 50:100. The temperature was raised to 170° C. in 10 min and kept warm for 10 min, then continued to be raised to 190° C. and kept warm for 1 h. After the reaction was completed, the temperature was completely cooled to room temperature and then taken out to obtain a black precipitate and a suspension.

[0034] (3) The product obtained in step (2) was centrifuged 5 times with deionized water and ethanol, and the precipitate was placed in a vacuum drying oven at 60° C. and dried for 10 h to obtain a black sodium vanadium fluorophosphate / carbon powder, denoted as NVPF / C-190-1 (see Figure 2 ).

[0035] Example 2

[0036] (1) Prepare the precursor reaction solution: Mix 20 mmol V2O5 and 60 mmol H2C2O4 (molar ratio 1:3), add deionized water to make the volume 40 mL, control the temperature to 70 °C water bath heating for 10 min, add 0.1 g C6H 12O6 (carbon source concentration is 0.011 mol·L -1 ), stirred for 10 min until it was completely dissolved, then added 40 mmol NH4H2PO4 and 60 mmol NaF (molar ratio, phosphate: vanadium = 1:1, sodium: vanadium = 3:2, fluorine: vanadium = 3:2) in sequence, continued to heat and stir in a 70°C water bath to obtain a transparent dark blue solution, added water to make the volume to 45 mL, after the temperature dropped to room temperature, added 3-fold diluted 15% concentrated hydrochloric acid dropwise to the dark blue solution, and adjusted the pH to 5.0.

[0037] (2) The solution obtained in step (1) was placed in a reactor of a microwave hydrothermal parallel synthesizer, with the volume ratio of the solution to the container being 50:100. The program was set to raise the temperature to 170°C in 10 minutes and keep it warm for 10 minutes, then continue to raise the temperature to 190°C and keep it warm for 1 hour. After the reaction was completed, it was taken out after it completely cooled to room temperature to obtain a dark green precipitate and suspension.

[0038] (3) The product obtained in step (2) was centrifuged 5 times using deionized water and ethanol, and the precipitate was placed in a vacuum drying oven at 60° C. for 10 h to obtain a dark green sodium vanadium fluorophosphate / carbon powder, recorded as NVPF / C-190-2.

[0039] Example 3

[0040] (1) Prepare the precursor reaction solution: Mix 40 mmol V2O5 and 100 mmol H2C2O4 (molar ratio 1:2.5), add deionized water to make the volume 50 mL, control the temperature to 70 °C water bath heating for 10 min, continue heating and stirring while adding 0.5 g C6H 12 O6 (carbon source concentration is 0.046 mol·L -1 ), stirred for 10 min until it was completely dissolved, then added 80 mmol NH4H2PO4 and 120 mmol NaF (molar ratio, phosphate: vanadium = 1:1, sodium: vanadium = 3:2, fluorine: vanadium = 3:2) in sequence, continued to heat and stir in a water bath at 80°C to obtain a transparent dark blue solution, added water to make the volume to 55 mL, after the temperature dropped to room temperature, added 3-fold diluted 15% concentrated hydrochloric acid dropwise to the dark blue solution, and adjusted the pH to 3.2.

[0041] (2) The solution obtained in step (1) was placed in a reactor of a microwave hydrothermal parallel synthesizer, with the volume ratio of the solution to the container being 60:100. The program was set to raise the temperature to 170° C. in 10 min and keep it warm for 10 min, then continue to raise the temperature to 210° C. and keep it warm for 50 min. After the reaction was completed, the temperature was completely cooled to room temperature and then taken out to obtain a dark green precipitate and suspension.

[0042] (3) The product obtained in step (2) was centrifuged 5 times using deionized water and ethanol, and the precipitate was placed in a vacuum drying oven at 70° C. to obtain a dark green sodium vanadium fluorophosphate / carbon powder, recorded as NVPF / C-210-3.

[0043] Example 4

[0044] (1) Prepare the precursor reaction solution: Mix 40 mmol V2O5 and 120 mmol H2C2O4 (molar ratio 1:3), add deionized water to make the volume 50 mL, control the temperature to 80 °C water bath heating for 10 min, continue heating and stirring while adding 2 g C6H 12 O6 (carbon source concentration is 0.185 mol·L -1 ), stirred for 10 min until it was completely dissolved, then added 80 mmol NH4H2PO4 and 120 mmol NaF (molar ratio, phosphate: vanadium = 1:1, sodium: vanadium = 3:2, fluorine: vanadium = 3:2) in sequence, continued to heat and stir in a water bath at 80°C to obtain a transparent dark blue solution, added water to make the volume to 55 mL, after the temperature dropped to room temperature, added 3-fold diluted 15% concentrated hydrochloric acid dropwise to the dark blue solution, and adjusted the pH to 5.0.

[0045] (2) The solution obtained in step (1) was placed in a reactor of a microwave hydrothermal parallel synthesizer, with the volume ratio of the solution to the container being 60:100. The program was set to raise the temperature to 170°C in 10 minutes and keep it warm for 10 minutes, then continue to raise the temperature to 210°C and keep it warm for 50 minutes. After the reaction was completed, the temperature was completely cooled to room temperature and then taken out to obtain a black precipitate and a suspension.

[0046] (3) The product obtained in step (2) was centrifuged 5 times using deionized water and ethanol, and the precipitate was placed in a vacuum drying oven at 60° C. for 13 h to obtain a black sodium vanadium fluorophosphate / carbon powder, recorded as NVPF / C-210-4.

[0047] Example 5

[0048] (1) Prepare the precursor reaction solution: Mix 20 mmol NH4VO3 and 30 mmol H2C2O4 (vanadium: reducing agent molar ratio 2:3), add deionized water to make the volume 40 mL, control the temperature to 80 ° C water bath heating for 10 min, continue heating and stirring while adding 0.1 g C6H 12 O6 (carbon source concentration is 0.011 mol·L -1), stirred for 10 min until it was completely dissolved, then added 20 mmol NH4H2PO4 and 60 mmol NaF (molar ratio, phosphate: vanadium = 1:1, sodium: vanadium = 3:2, fluorine: vanadium = 3:2) in sequence, continued to heat and stir in a water bath at 80°C to obtain a transparent dark blue solution, added water to make the volume to 45 mL, after the temperature dropped to room temperature, added 3-fold diluted 15% concentrated hydrochloric acid dropwise to the dark blue solution, and adjusted the pH to 5.0.

[0049] (2) The solution obtained in step (1) was placed in a reactor of a microwave hydrothermal parallel synthesizer, with the volume ratio of the solution to the container being 60:100. The program was set to raise the temperature to 170°C in 10 minutes and keep it warm for 10 minutes, then continue to raise the temperature to 210°C and keep it warm for 50 minutes. After the reaction was completed, the temperature was completely cooled to room temperature and then taken out to obtain a black precipitate and a suspension.

[0050] (3) The product obtained in step (2) was centrifuged 5 times using deionized water and ethanol, and the precipitate was placed in a vacuum drying oven at 60° C. for 13 h to obtain a black sodium vanadium fluorophosphate / carbon powder.

[0051] Example 6

[0052] (1) Prepare the precursor reaction solution: Mix 40 mmol NH4VO3 and 60 mmol H2C2O4 (vanadium: reducing agent molar ratio 2:3), add deionized water to make the volume 50 mL, control the temperature to 80 ° C water bath heating for 10 min, continue heating and stirring while adding 1 g C6H 12 O6 (carbon source concentration is 0.0925 mol·L -1 ), stirred for 10 min until it was completely dissolved, then added 40 mmol NH4H2PO4 and 60 mmol NaF (molar ratio, phosphate: vanadium = 1:1, sodium: vanadium = 3:2, fluorine: vanadium = 3:2) in sequence, continued to heat and stir in a water bath at 80°C to obtain a transparent dark blue solution, added water to make the volume to 55 mL, after the temperature dropped to room temperature, added 3-fold diluted 15% concentrated hydrochloric acid dropwise to the dark blue solution, and adjusted the pH to 5.0.

[0053] (2) The solution obtained in step (1) was placed in a reactor of a microwave hydrothermal parallel synthesizer, with the volume ratio of the solution to the container being 60:100. The program was set to raise the temperature to 170°C in 10 minutes and keep it warm for 10 minutes, then continue to raise the temperature to 210°C and keep it warm for 50 minutes. After the reaction was completed, the temperature was completely cooled to room temperature and then taken out to obtain a black precipitate and a suspension.

[0054] (3) The product obtained in step (2) was centrifuged 5 times using deionized water and ethanol, and the precipitate was placed in a vacuum drying oven at 60° C. for 13 h to obtain a black sodium vanadium fluorophosphate / carbon powder.

[0055] Comparative Example 1

[0056] (1) Preparation of precursor reaction solution: 20 mmol V2O5 and 50 mmol H2C2O4 (vanadium: reducing agent molar ratio 1:2.5) were mixed, deionized water was added to make up to 40 mL, and the temperature was controlled to be heated in a water bath at 70°C for 10 min. Then 40 mmol NH4H2PO4 and 60 mmol NaF (molar ratio, phosphate: vanadium = 1:1, sodium: vanadium = 3:2, fluorine: vanadium = 3:2) were added in sequence, and the mixture was continued to be heated in a water bath at 70°C with stirring to obtain a transparent dark blue solution, and water was added to make up to 45 mL. After the temperature dropped to room temperature, 15% concentrated hydrochloric acid diluted 3 times was added dropwise to solution 3 to adjust the pH to 3.2.

[0057] (2) The solution obtained in step (1) is placed in a common hydrothermal reactor, and the reactor is placed in a constant temperature box with a blast at 10°C / min. -1 The temperature was raised to 190°C at a rate of 100 °C and kept at this temperature for 20 h. After the temperature was completely reduced to room temperature, a light green precipitate and suspension were obtained.

[0058] (3) The product obtained in step (2) was centrifuged 5 times using deionized water and ethanol, the supernatant was discarded, and the precipitate was placed in a vacuum drying oven at 60° C. for 12 h to obtain a light green sodium vanadium fluorophosphate powder.

[0059] (4) The light green sodium vanadium phosphate powder obtained in step (3) is carbon coated by mixing 9.0 g of sodium vanadium fluorophosphate with 1.0 g of Ketjen black in a mass ratio of 9:1, adding 50 g of zirconium oxide ball milling beads, rotating at a speed of 400 rpm, forward ball milling for 15 min, pausing for 5 min, and then reverse ball milling for 15 min, ensuring that the ball milling time reaches 60 min, to obtain black sodium vanadium fluorophosphate / carbon powder.

[0060] Comparative Example 2

[0061] (1) Prepare the precursor reaction solution: Mix 20 mmol V2O5 and 50 mmol H2C2O4 (vanadium: reducing agent molar ratio 1:2.5), add deionized water to make the volume 40 mL, control the temperature to 70 ° C water bath heating for 10 min, continue heating and stirring while adding 1 g C6H 12 O6 (carbon source concentration is 0.11 mol·L -1), stir for 10 min until it is completely dissolved, then add 40 mmol NH4H2PO4 and 60 mmol NaF (phosphate: vanadium source = 1:1, sodium source: vanadium source = 3:2, fluorine source: vanadium source = 3:2) in sequence, continue to heat and stir in a water bath at 80°C to obtain a transparent dark blue solution, add water to make the volume to 45 mL, after the temperature drops to room temperature, add 3-fold diluted 15% concentrated hydrochloric acid dropwise into the dark blue solution, and adjust the pH to 3.2.

[0062] (2) The solution obtained in step (1) was placed in a common hydrothermal reactor, and the reactor was placed in a constant temperature box with a blast for 10 min. -1 The temperature was raised to 180°C at a rate of 100 °C and kept at this temperature for 20 h. After the temperature was completely reduced to room temperature, a black precipitate and a suspension were obtained.

[0063] (3) The product obtained in step (2) was centrifuged 5 times with deionized water and ethanol, and the precipitate was placed in a vacuum drying oven at 60° C. and dried for 13 h to obtain a black sodium vanadium fluorophosphate / carbon powder (see Figure 2 ).

[0064] Comparative Example 3

[0065] (1) Prepare the precursor reaction solution: Mix 40 mmol V2O5 and 120 mmol H2C2O4 (vanadium: reducing agent molar ratio 1:3), add deionized water to make the volume 50 mL, control the temperature to 80 ° C water bath heating for 10 min, continue heating and stirring while adding 2 g C6H 12 O6 (carbon source concentration is 0.185 mol·L -1 ), stirred for 10 min until it was completely dissolved, then added 80 mmol NH4H2PO4 and 120 mmol NaF (molar ratio, phosphate: vanadium = 1:1, sodium: vanadium = 3:2, fluorine: vanadium = 3:2) in sequence, continued to heat and stir in a water bath at 80°C to obtain a transparent dark blue solution, added water to make the volume to 55 mL, after the temperature dropped to room temperature, added 3-fold diluted 15% concentrated hydrochloric acid dropwise to the dark blue solution, and adjusted the pH to 2.5.

[0066] (2) The solution obtained in step (1) was placed in a reactor of a microwave hydrothermal parallel synthesizer, with the volume ratio of the solution to the container being 60:100. The program was set to raise the temperature to 170°C in 10 minutes and keep it warm for 10 minutes, then continue to raise the temperature to 210°C and keep it warm for 50 minutes. After the reaction was completed, the temperature was completely cooled to room temperature and then taken out to obtain a black precipitate and a suspension.

[0067] (3) The product obtained in step (2) was centrifuged 5 times using deionized water and ethanol, and the precipitate was placed in a vacuum drying oven at 60° C. for 13 h to obtain a black sodium vanadium fluorophosphate / carbon powder.

[0068] Comparative Example 4

[0069] (1) Prepare the precursor reaction solution: Mix 40 mmol V2O5 and 120 mmol H2C2O4 (vanadium: reducing agent molar ratio 1:3), add deionized water to make the volume 50 mL, control the temperature to 80 ° C water bath heating for 10 min, continue heating and stirring while adding 2 g C6H 12 O6 (carbon source concentration is 0.185 mol·L -1 ), stirred for 10 min until it was completely dissolved, then added 80 mmol NH4H2PO4 and 120 mmol NaF (molar ratio, phosphate: vanadium = 1:1, sodium: vanadium = 3:2, fluorine: vanadium = 3:2) in sequence, continued to heat and stir in a water bath at 80°C to obtain a transparent dark blue solution, added water to make the volume to 55 mL, after the temperature dropped to room temperature, added 3-fold diluted 15% concentrated hydrochloric acid dropwise to the dark blue solution, and adjusted the pH to 8.0.

[0070] (2) The solution obtained in step (1) was placed in a reactor of a microwave hydrothermal parallel synthesizer, with the volume ratio of the solution to the container being 60:100. The program was set to raise the temperature to 170°C in 10 minutes and keep it warm for 10 minutes, then continue to raise the temperature to 210°C and keep it warm for 50 minutes. After the reaction was completed, the temperature was completely cooled to room temperature and then taken out to obtain a black precipitate and a suspension.

[0071] (3) The product obtained in step (2) was centrifuged 5 times using deionized water and ethanol, and the precipitate was placed in a vacuum drying oven at 60° C. for 13 h to obtain a black sodium vanadium fluorophosphate / carbon powder.

[0072] Comparative Example 5

[0073] (1) Prepare the precursor reaction solution: Mix 40 mmol V2O5 and 120 mmol H2C2O4 (vanadium: reducing agent molar ratio 1:3), add deionized water to make the volume 50 mL, control the temperature to 80 ° C water bath heating for 10 min, continue heating and stirring while adding 2 g C6H 12 O6 (carbon source concentration is 0.185 mol·L -1 ), stirred for 10 min until it was completely dissolved, then added 80 mmol NH4H2PO4 and 120 mmol NaF (molar ratio, phosphate: vanadium = 1:1, sodium: vanadium = 3:2, fluorine: vanadium = 3:2) in sequence, continued to heat and stir in a water bath at 80°C to obtain a transparent dark blue solution, added water to make the volume to 55 mL, after the temperature dropped to room temperature, added 3-fold diluted 15% concentrated hydrochloric acid dropwise to the dark blue solution, and adjusted the pH to 6.0.

[0074] (2) The solution obtained in step (1) was placed in a reactor of a microwave hydrothermal parallel synthesizer, with the volume ratio of the solution to the container being 60:100. The program was set to raise the temperature to 170°C in 10 minutes and keep it warm for 10 minutes, then continue to raise the temperature to 240°C and keep it warm for 50 minutes. After the reaction was completed, the temperature was completely cooled to room temperature and then taken out to obtain a black precipitate and a suspension.

[0075] (3) The product obtained in step (2) was centrifuged 5 times using deionized water and ethanol, and the precipitate was placed in a vacuum drying oven at 60° C. for 13 h to obtain a black sodium vanadium fluorophosphate / carbon powder.

[0076] From the XRD patterns of sodium vanadium fluorophosphate / carbon powder obtained in Example 1 and Comparative Example 2, it can be seen that in Example 1, the vanadium source (V2O5), the reducing agent (H2C2O4), the carbon source (C6H 12 O6), phosphorus source (NH4H2PO4), sodium source and fluorine source (NaF) were heated and stirred to dissolve in deionized water, and then the pH was adjusted with hydrochloric acid to obtain a dark blue homogeneous solution, which was placed in a microwave hydrothermal parallel synthesizer and reacted at 190°C for 1h to finally obtain a carbon-coated sodium vanadium fluorophosphate composite positive electrode (NVPF / C). Compared with Comparative Example 2, Example 1 has better crystallinity, which confirms that microwave hydrothermal better promotes the crystal nucleus growth of NVPF.

[0077] The sodium vanadium fluorophosphate / carbon obtained in the above examples and comparative examples was used as the positive electrode material, sodium as the negative electrode, a 1 m NaPF6 / G2 electrolyte prepared with sodium hexafluorophosphate and diethylene glycol dimethyl ether was used, and a button cell was assembled using glass fiber (GFD) as the separator for testing. See Table 1 and Figure 3-5 .

[0078] Table 1

[0079]

[0080]

[0081] As can be seen from Table 1, the specific capacities of each group of experiments at different rates are summarized. At the same time, it can be seen from the positive electrode materials obtained in Examples 1-6 and Comparative Examples 3-5 that the pH value and temperature will affect the performance of the material by affecting the nucleation and carbon coating process of the material. When the temperature is too high, it may cause certain damage to the material structure. When the pH is too high, some side reactions may be generated, and the target product is unstable. However, under certain conditions, the sodium vanadium fluorophosphate / carbon composite positive electrode synthesized has excellent rate performance, among which, the pH of 3.2 improves the reaction rate and the purity of the target product, and the sodium vanadium fluorophosphate / carbon composite positive electrode synthesized at a temperature of 190°C has uniform nucleation and a complete structure, and has better rate performance.

[0082] like Figure 3The sodium vanadium fluorophosphate / carbon synthesized in Example 1 and Comparative Example 1 was used as the positive electrode to assemble the battery and perform charge and discharge tests at different rates (1C, 2C, 5C, 10C, 1C). The figure shows the comparison of the rate and coulomb efficiency. Figure 3 The rate performance comparison in Figure 2 shows that the sodium vanadium fluorophosphate / carbon composite cathode prepared by microwave-assisted synthesis using the one-pot method has better rate performance and specific capacity. Figure 4 , showing the charge and discharge curve of Example 3 under 1C conditions, the charge and discharge platform of sodium vanadium fluorophosphate can be clearly observed, proving that the sodium vanadium fluorophosphate / carbon positive electrode with excellent performance can be successfully synthesized at this ratio.

[0083] Figure 5 The sodium vanadium fluorophosphate / carbon cathode assembled battery synthesized in Example 2 was subjected to charge and discharge tests at different rates (1C, 2C, 5C, 10C, 15C, 1C). The figure shows the rate performance and coulombic efficiency of the battery assembled with the sodium vanadium fluorophosphate / carbon cathode synthesized by this method. Figure 5 It can be seen that the same hydrothermal synthesis method is used with glucose as the carbon source. Figure 3 Compared with the sodium vanadium fluorophosphate / carbon positive electrode synthesized by one-pot microwave hydrothermal method in Example 1, the rate performance is extremely poor and the coulombic efficiency is lower due to incomplete carbon coating.

[0084] In summary, the "one-pot" microwave-assisted synthesis method of the present invention can greatly shorten the time required for synthesizing sodium vanadium fluorophosphate and carbon coating, improve the synthesis efficiency, and meet the demand for efficient synthesis methods in the field of battery material synthesis. Secondly, the method of the present invention overcomes the disadvantage of uneven heating of the traditional hydrothermal method, improves the purity and crystallinity of the synthesized sodium vanadium fluorophosphate, so that it has better electrochemical properties, and meets the demand for high-performance positive electrode materials in the field of sodium ion battery positive electrode materials. Finally, the method of the present invention simplifies the synthesis steps, reduces energy consumption and costs, and meets the demand for energy-saving, environmentally friendly, and low-cost synthesis methods in the field of microwave-assisted synthesis technology. See Table 2. Therefore, the present invention has broad market prospects and application value.

[0085] Table 2

[0086]

Claims

1. A one-pot method for preparing sodium vanadium fluorophosphate / carbon composite positive electrode material, characterized in that: The raw materials for synthesizing sodium vanadium fluorophosphate are mixed in stoichiometric amounts, and then a reducing agent and a carbon source are added, mixed and dissolved to form a transparent solution, and then the solution is reacted under microwave conditions at 160° C. to 220° C. to obtain a sodium vanadium fluorophosphate / carbon composite positive electrode material.

2. The method for preparing sodium vanadium fluorophosphate / carbon composite positive electrode material by one-pot process according to claim 1, characterized in that: The vanadium source and the reducing agent in the synthetic sodium vanadium fluorophosphate are mixed and dissolved with deionized water, and a carbon source is added during the dissolution until a homogeneous solution is formed. Then, a phosphorus source, a sodium source and a fluorine source are added in sequence according to the stoichiometric amount and stirred to form a transparent solution. The solution is reacted at 160° C. to 220° C. under microwave conditions. After the reaction is completed, it is naturally cooled to room temperature, centrifuged with deionized water and ethanol for multiple times, and then vacuum dried to obtain the final product.

3. The method for preparing sodium vanadium fluorophosphate / carbon composite positive electrode material by one-pot process according to claim 1 or 2, characterized in that: (1) preparing a precursor reaction solution: mixing a vanadium source and a reducing agent with deionized water, heating and stirring until completely dissolved, adding a carbon source during the complete dissolution process, and continuing to stir until a homogeneous solution is formed, and then adding a phosphorus source, a sodium source, and a fluorine source to the homogeneous solution, and continuing to stir under the above heating conditions until completely dissolved into a transparent solution, and adjusting the system to a weak acid after a transparent solution is formed; (2) Microwave hydrothermal synthesis of precursor products: The transparent solution obtained in step (1) is placed in a microwave hydrothermal parallel synthesizer, heated to 160°C to 220°C and reacted under microwave conditions. After the reaction, it is cooled to room temperature and centrifuged multiple times with deionized water and ethanol. The precipitate after centrifugation is vacuum dried to obtain a sodium vanadium fluorophosphate / carbon composite positive electrode material.

4. The method for preparing sodium vanadium fluorophosphate / carbon composite positive electrode material by one-pot process according to claim 3, characterized in that: In the step (1), during the process of forming a transparent solution, the heating temperature and stirring conditions of each dissolution process are the same, the heating temperature is 60-80° C., and the stirring condition is 250-800 rpm.

5. The method for preparing sodium vanadium fluorophosphate / carbon composite positive electrode material by one-pot process according to claim 3, characterized in that: The concentration of vanadium in the system in step (1) is controlled at 0.33 to 1.80 mol·L -1 The concentration of the reducing agent is controlled at 0.83~5.76mol·L -1 , carbon source concentration is 0.11~1.60mol·L -1 The concentration of phosphate is 0.17~1.60mol·L -1 The concentration of fluorine source is 0.83~5.76mol·L -1 , the concentration of sodium source is 0.83~5.76mol·L -1 .

6. The method for preparing sodium vanadium fluorophosphate / carbon composite positive electrode material by one-pot process according to claim 3 or 5, characterized in that: The vanadium source is one or more of vanadium pentoxide, ammonium metavanadate, sodium vanadate and sodium metavanadate; the reducing agent is oxalic acid or citric acid; the carbon source is glucose or sucrose; the phosphorus source is one or more of ammonium dihydrogen phosphate, diammonium hydrogen phosphate and sodium dihydrogen phosphate; the fluorine source is sodium fluoride or ammonium fluoride; and the sodium source is one or more of a vanadium source, a phosphorus source or a sodium-containing substance in a fluorine source, sodium oxalate, sodium carbonate and sodium bicarbonate.

7. The one-pot method for preparing sodium vanadium fluorophosphate / carbon composite positive electrode material according to claim 3, characterized in that: In step (1), hydrochloric acid, sulfuric acid, nitric acid, acetic acid or lactic acid may be used to adjust the system to a weak acid state, and the pH value may be adjusted to a range between 3.0 and 6.

0.

8. The method for preparing sodium vanadium fluorophosphate / carbon composite positive electrode material by one-pot process according to claim 3, characterized in that: In the step (2), the volume ratio of the transparent solution to the reactor of the microwave hydrothermal parallel synthesizer is (35-60):100; the microwave frequency is 2450 MHz, the reaction temperature is 160° C.-220° C., and the reaction time is 60 min-120 min.

9. Use of the sodium vanadium fluorophosphate / carbon composite positive electrode material prepared by the method according to claim 1 in a sodium ion battery.

Citation Information

Patent Citations

  • Preparation of Na3V2(PO4)2F3 / carbon compound and application of same

    CN109755489A